The Operation of Two Decarboxylases, Transamination, and Partitioning of C4 Metabolic Processes between Mesophyll and Bundle Sheath Cells Allows Light Capture To Be Balanced for the Maize C4 Pathway . Issue 1 (19th November 2013) - Bellasio, Chandra; Griffiths, Howard
Abstract : Light quality was used to manipulate ATP supply and demand between C4 pathway mesophyll and bundle sheath, and the results are consistent with a metabolic model that explains the requirement for two decarboxylases and the partitioning of metabolic activities in maize . Abstract: The C4 photosynthesis carbon-concentrating mechanism in maize ( Zea mays ) has two CO2 delivery pathways to the bundle sheath (BS ; via malate or aspartate), and rates of phosphoglyceric acid reduction, starch synthesis, and phospho enol pyruvate regeneration also vary between BS and mesophyll (M ) cells. The theoretical partitioning of ATP supply between M and BS cells was derived for these metabolic activities from simulated profiles of light penetration across a leaf, with a potential 3-fold difference in the fraction of ATP produced in the BS relative to M (from 0.29 to 0.96). A steady-state metabolic model was tested using varying light quality to differentially stimulate M or BS photosystems. CO2 uptake, ATP production rate ( J  ATP ; derived with a low oxygen/chlorophyll fluorescence method), and carbon isotope discrimination were measured on plants under a low light intensity, which is considered to affect C4 operating efficiency. The light quality treatments did not change the empirical ATP cost of gross CO2 assimilation ( J  ATP / GA ). Using the metabolic model, measured J  ATP / GA was compared with the predicted ATP demand as metabolic functions were varied between M and BS . Transamination and the two decarboxylase systems (NADP-malic enzyme and phospho enol pyruvate carboxykinase) were critical for matching ATP and reduced NADP demand in BS and M when light capture was varied under contrasting light qualities.